2017
DOI: 10.32677/ijch.2017.v04.i04.026
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Incidence of Retinopathy of Prematurity in High-Risk Neonates and the Risk Factors Associated With the Disease

Abstract: Background: Retinopathy of prematurity (ROP) is a complex disease of the developing retinal vasculature in premature infant. The challenge in India is that a large number of neonatal intensive care units (NICUs) don't have an effective ROP screening strategy. Objective: To measure the incidence of ROP in neonates with gestational age (≤32 weeks) or weighing <2000 g with risk factors and evaluation of risk factor associated with ROP. Materials and Methods: This prospective study was conducted in the Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…A statistically significant association was found between oxygen supplementation and the development of ROP (p-value = 0.0251). This is comparable to various other studies showing oxygen therapy as a significant risk for ROP [ 6 , 7 , 9 ]. One of the reasons why the incidence of ROP is decreasing in developed countries is due to their strict guidelines and monitoring of oxygen therapy provided to infants, which is lacking in countries like India.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A statistically significant association was found between oxygen supplementation and the development of ROP (p-value = 0.0251). This is comparable to various other studies showing oxygen therapy as a significant risk for ROP [ 6 , 7 , 9 ]. One of the reasons why the incidence of ROP is decreasing in developed countries is due to their strict guidelines and monitoring of oxygen therapy provided to infants, which is lacking in countries like India.…”
Section: Discussionsupporting
confidence: 91%
“…This is in concurrence with studies done by Patel et al in Vadodara [ 6 ] between 2017 and 2018 with an incidence of 24.1% of the 284 neonates screened for ROP and by Thakre et al in Maharashtra [ 7 ], where the incidence of ROP was found to be 27.73% of the 119 neonates screened. The incidence in the present study was found to be lower as compared to the study by Tekchandani et al [ 8 ] conducted at a tertiary care institute in North India during 2013-2017 in which incidence was 32.3% and higher when compared with Singh et al [ 9 ], who reported an incidence of 19% in their study conducted in Ajmer in 2016. The discrepancies in observation may be due to the varying sample size taken, differences in the study duration, and geographical areas where the studies were conducted.…”
Section: Discussioncontrasting
confidence: 83%
“…In a multicenter study conducted in our country, it was found out that the incidence of ROP was 30% (10). The incidence of ROP is 17.9% in the USA, between 19% and 46% in India and 31.3% in Portugal (15)(16)(17)(18). According to our results, ROP is a serious problem that may cause potentially blindness for premature babies unless the neonatal intensive care services would be eligible conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of severe ROP is 8.31% in the USA, 5% in Turkey and between 4% and 9% in India (10,(15)(16)(17). We considered treatment in 8.8% of the screened infants due to the severe ROP.…”
Section: Discussionmentioning
confidence: 99%